2018
DOI: 10.3390/molecules23071690
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Analysis of 17β-Estradiol-Aptamer Interactions: A Molecular Dynamics Simulation Study

Abstract: Micro-pollutants such as 17β-Estradiol (E2) have been detected in different water resources and their negative effects on the environment and organisms have been observed. Aptamers are established as a possible detection tool, but the underlying ligand binding is largely unexplored. In this study, a previously described 35-mer E2-specific aptamer was used to analyse the binding characteristics between E2 and the aptamer with a MD simulation in an aqueous medium. Because there is no 3D structure information ava… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 82 publications
2
22
0
Order By: Relevance
“…These results are in agreement with a molecular dynamics simulation study that highlighted that the 5’ and 3’ ends of E2‐aptamer are not interacting with E2 and can be thus used for aptamer functionalization or immobilization. Furthermore, the described results are consistent with previous experiment involving a salan complex as electroactive label for the same aptamer [11,40] …”
Section: Resultssupporting
confidence: 92%
“…These results are in agreement with a molecular dynamics simulation study that highlighted that the 5’ and 3’ ends of E2‐aptamer are not interacting with E2 and can be thus used for aptamer functionalization or immobilization. Furthermore, the described results are consistent with previous experiment involving a salan complex as electroactive label for the same aptamer [11,40] …”
Section: Resultssupporting
confidence: 92%
“…Although several groups have sought to improve protein-RNA docking (16,17), whole-molecule docking approaches are still mostly focused on proteins (18). Combining the techniques of RNA structure prediction, docking, and molecular modeling, several works have sought to design RNA aptamers in silico, using a structure-based procedure (19,20); however, these methodologies have produced varied results. In this work, we propose an aptamer design framework composed of three major phases, including constructing the aptamer structures, predicting their binding conformations, and optimizing their binding through mutations.…”
mentioning
confidence: 99%
“…The lower RMSD values of A380I indicated enhanced stability of the mutant strain after ligand binding. The radius of gyration (Rg, Figure 4B) represents the overall size of the protein [23]. Rg values of the complex system WT-AK + Asp + ATP + Lys showed that inhibitors (Lys) reduced the flexibility of the protein (remaining mostly 23.0 Å, Figure 4E), whereas Rg values of A380I + Asp + ATP + Lys system showed significant fluctuations (remaining mostly 24.3–25 Å, Figure 4E) during the simulation process, indicating that mutation of alanine (A) into isoleucine (I) near the inhibitor would restore the flexibility and activity of CpAK.…”
Section: Resultsmentioning
confidence: 99%